Implicit iterative algorithms for continuous Markovian jump Lyapunov equations - Wu, A.; Duan, G.; Liu, Wan-Quan (Institute of Electrical and Electronics Engineers, 2016)
© 2015 IEEE.In this technical note, implicit iterative algorithms with some tunable parameters are developed to solve the coupled Lyapunov matrix equations associated with continuous-time Markovian jump linear systems. A significant feature of the proposed algorithms is that the iterative sequences are updated by using not only the information in the last step, but also the information in the current step and the previous steps. Also the convergence rate of the proposed algorithms can be significantly improved by choosing appropriate parameters in the algorithms.